Analisis Kreatifitas Produk Klanting Terhadap Keberhasilan Perkembangan UKM di Tahai Baru Kecamatan Maliku Kabupaten Pulang Pisau - Kuwing Baboe; Maria Haryulin Astuti; Fendy Hariatama; Rinto Alexandro (FKIP, Universitas Palangka Raya, 2023)
Improved quality and creativity of workers, as reflected by the average level of education which is getting better, has a positive impact on work productivity. Likewise, efforts to improve skills and workforce training accompanied by the application of appropriate technology have an impact on increasing work productivity. Every business or business wants to get business success that utilizes local potential, namely local wisdom in the area, a business is said to be successful if it earns profit, even though profit is not the only aspect that is assessed from the success of a business, but the reason profit is an important factor is because profit is the goal of people who do business. If there is a decrease or instability in profits, the business will find it difficult to operate its business activities and maintain its business resilience. The purpose of this study was to analyze and describe Production Creativity on the Success of Small and Medium Enterprises (UKM) of Klanting in Tahai Baru Village, Maliku District, Pulang Pisau Regency. This type of research is qualitative research. This study involved 4 (four) informants. The results of the study show that production creativity influences business success. Overall there was an increase in sales and turnover. The new production creativity is more advanced than the old creativity. Creative ideas often arise when entrepreneurs see something old and think something new and different. Therefore creativity is creating something from nothing.